Central sleep apnoea syndrome in patients with chronic heart disease: a critical review of the current literature. Issue 6 (1st June 2002) - Köhnlein, T; Welte, T; Tan, L B; Elliott, M W
Abstract : The prevalence, prognosis, clinical presentation, pathophysiology, diagnosis, and treatment of the central sleep apnoea syndrome (CSAS) are reviewed and its relationship with congestive heart failure (CHF) is discussed. Adequately powered trials are needed with survival and health status as end points to establish whether correction of sleep related breathing abnormalities improves the outcome in patients with CHF.